2017
DOI: 10.3892/mmr.2017.6599
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of follicle stimulating hormone receptor mRNA and protein in pregnancies complicated by pre-eclampsia

Abstract: Expression and function of the follicle‑stimulating hormone receptor (FSHR) are traditionally thought to be limited to the ovary in females. However, recent studies have indicated that the FSHR is also expressed in endothelial cells of the placental vasculature, and that the haploinsufficiency of the feto‑placental FSHR impaired the growth of the mouse placenta. The aim of the current study was to investigate the placental expression of FSH and FSHR in pregnancies complicated by pre‑eclampsia. Placental tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Several studies have been conducted to investigate the effect of gonadotropin in PE. For example, Li et al observed that the expression of the mRNA of the FSH receptor is reduced in PE [ 23 ], while Reisinger et al reported that gonadotropins, such as FSH and LH, are angiogenic factors and play an important role in PE [ 24 ]. Another biological process associated with PE is the SMAD pathway, which is well known for its relationship with epithelial mesenchymal transition (EMT) and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted to investigate the effect of gonadotropin in PE. For example, Li et al observed that the expression of the mRNA of the FSH receptor is reduced in PE [ 23 ], while Reisinger et al reported that gonadotropins, such as FSH and LH, are angiogenic factors and play an important role in PE [ 24 ]. Another biological process associated with PE is the SMAD pathway, which is well known for its relationship with epithelial mesenchymal transition (EMT) and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%